Building Excellence Among Muslim Entrepreneurs Through Digital Innovation: The Role of Capabilities and Knowledge Sharing in the Digital Era - Sarman, Rohmat; Jusuf, Eddy; Suteja, Jaja; Juniarti, Atty Tri (Universitas Brawijaya, Indonesia, 2024)
This research addresses the urgent need for Nahdliyin entrepreneurs in Indonesia to adopt digital innovation to remain competitive in the global market. Focusing on the role of entrepreneurial capabilities and knowledge sharing, this study explores how these factors foster digital innovation within the unique cultural framework of Muslim entrepreneurship. Using a quantitative design, data were collected from 400 Nahdliyin entrepreneurs in West Java through stratified random sampling and analyzed with Partial Least Square Structural Equation Modeling (PLS-SEM). Findings reveal that entrepreneurial capabilities significantly enhance knowledge sharing and that both capabilities and knowledge sharing positively impact digital innovation. Additionally, knowledge sharing mediates the relationship between entrepreneurial capabilities and digital innovation, highlighting its role as a crucial enabler. The study’s novelty lies in its focus on a culturally specific entrepreneurial community, offering fresh insights into how Muslim values foster collective learning and innovation. The study suggests that strengthening entrepreneurial skills and a knowledge-sharing culture in Muslim communities can drive digital innovation, aligning business growth with community and religious values. These findings have important implications for entrepreneurs, policymakers, and educators in enhancing economic growth in emerging Muslim markets.